Constraints and breeding priorities for increased sweetpotato utilization in Ghana - Baafi, E.; Manu-Aduening, J.A.; Carey, E.E.; Ofori, K.; Blay, E.T.; Gracen, V.E. (Canadian Center of Science and Education, 2015)
Sweetpotato is used in various food preparations in place of rice, cassava, yam and plantain in Ghana. In spite of this it does not have the same importance in Ghanaian diet as other root and tuber crops. Consumer taste, preference and acceptance are critical in determining the suitability of sweetpotato cultivars to any locality. A study was carried out in some selected communities of Ghana where sweetpotato is popular which span all five ecozones of Ghana in February, 2012. The main objective was to investigate why sweetpotato has low utilization compared with other root and tuber crops and to increase its utilization through breeding. The study employed Focus Group Discussion (FGD) followed by administration of Semi-structured Questionnaire (SSQ). Data collected were analysed using Genstat and Statistical Package for Social Sciences. Seventy-nine people consisting of 63% males and 37% females, and 178 people consisting of 52% female and 48% males were involved in the FGD and SSQ, respectively. Majority (94%) of farmers’ ranked sweetpotato from 1 to 5 among 24 cultivated crops. Only about 28% of consumers ate sweetpotato at least six days per week. The survey revealed that consumers in Ghana desired non-sweet, high dry matter sweetpotato cultivars. Therefore, there is need for Research and Development to adjust sweetpotato breeding objectives and selection procedures to develop high dry matter non-sweet sweetpotato varieties in Ghana